Peningkatan Nilai Ekonomi Dan Kelestarian Lingkungan Melalui Pengelolaan Limbah Pertanian Dan Rumah Tangga - Putu Ayu anjaswari; I Nyoman Suarna; Ida Kade Suparta (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2026)
Agriculture in Taman Bali Hamlet, Sepakek Village, Pringgarata Sub-district, Central Lombok Regency is facing a decline in crop yields due to excessive use of chemical fertilizers. To overcome this problem, community service activities aim to increase community understanding of the management of agricultural and household waste into organic fertilizer, in line with the principles of Tri Hita Karana. The methods used include observation, interviews, training, and field practice. The program began with a site survey, followed by socialization and discussion with resource persons from the NTB Agriculture and Forestry Office, as well as the practice of making organic fertilizer using the Lindi method. The results of the activity showed that the community, especially teenagers and adults, showed increased understanding and enthusiasm in managing waste into organic fertilizer. The evaluation of the activity indicated that this socialization was effective in introducing waste management methods that not only reduce waste but also have the potential to improve soil fertility and the economic welfare of the community.